Monitoring and predicting disease activity in autoimmune pancreatitis with the M-ANNHEIM-AiP-Activity-Score - Hirth, Michael; Vujasinovic, Miroslav; Münch, Markus; Weiß, Christel; Ebert, Matthias; Schneider, Alexander (Pancreatology, 2018)
Background & objectives: Autoimmune pancreatitis (AiP) is treated by immunosuppressive therapy. Exact description of disease activity of AiP is essential in clinical practice and research, but a score to describe the disease activity is missing. Thus, we aimed to establish an activity score of AiP. Methods: We retrospectively studied long-term disease courses of 29 patients with AiP (Mannheim, Germany), receiving corticosteroid treatment (CST) by analyzing 613 treatment appointments. Two assumptions were made: First, disease activity is higher at emergency treatments; second, disease activity drops under CST. In all patients, we evaluated established activity- and classification-systems of chronic pancreatitis (cP). Based on the most suitable system, we established an activity score of AiP by including AiP-specific parameters identified from our long-term disease courses and the literature. The new AiP-specific activity score was validated in an external cohort of 14 patients with AiP (Stockholm, Sweden). Results: Within published activity indexes of cP, the M-ANNHEIM-classification most significantly correlated with emergency- and treatment-dependent disease activities (p < 0.001 and p < 0.01, conditional-logistic-regression-analysis). Significant correlations of disease activity were found for several clinical parameters (biliary involvement, extrapancreatic lesions, acute pancreatitis, focal pancreatic mass, pancreatic sausage/mass, focal enlargement, ascites; p < 0.05, Wilcoxon-signed-rank-test). Based on these data and disease features from the literature, the M-ANNHEIM-AiP-Activity-Score (MAAS) was established. CST-induced reduction of MAAS disease activity of more than 60% was associated with lower relapse rates (p < 0.05; Chi-Square-test). The results were validated in the external patient cohort. Conclusion: The MAAS might represent a useful tool to monitor AiP.
Available online 25 October 2017
Gesehen am 12.07.2018